Église et scandales : Trollope ou la condamnation de l’excès - Hervé Picton (Cahiers Victoriens et Edouardiens)
The 1830s were marked by a host of Church scandals widely reported by the press and in particular by the radical journalist John Wade in his Extraordinary Black Book published anonymously in 1831. Wade lashes out at idleness, pluralism and absenteeism and exposes shocking disparities in income among the clergy of the established Church. The most blatant abuses were addressed—with mixed results—by the Ecclesiastical Commission created in 1835 to reform the Church. Yet, reform was so slow to implement that when Trollope’s first ecclesiastical novel, The Warden, was published twenty years later, many of the abuses denounced by Wade endured. Trollope, by his own account a « conservative Liberal », was in reality a moderate who could not suffer excess — in religion as well as in politics. Until the end of his life he relentlessly inveighed against the abuses of the « high and dry, » that worldly type of clergy he satirized mercilessly, and denounced corruption, idleness and nepotism, along with the shameless exploitation of poor curates. He did, however, condemn just as vigorously the excesses of the reformist press, the exaggerations of some of his fellow-novelists (Dickens and Carlyle), and the irresponsibility of radical demagogues bent on undermining the Church.